Patient Perceptions on the Role of Informal Caregiver Support in Managing Advanced COPD - Barbara Gonçalves PhD; Eileen Harkess-Murphy PhD; Audrey Cund PhD; Caroline Sime PhD; Joanne Lusher PhD (Journal of Patient Experience, 2025)
People with advanced chronic obstructive pulmonary disease (COPD) experience a high physical burden which limits their activities and leads to social isolation, loneliness, and burdening social networks, with informal caregivers playing a crucial role in managing their condition. This study explored the views of people with COPD on informal caregiving, highlighting lifestyle adjustments and caregiver–patient dynamics. A qualitative study using semistructured interviews was conducted with 22 participants with advanced COPD recruited from palliative care services. Three themes emerged: patient autonomy, adapting to life under medical constraints and caregiver's understanding of patients’ needs. Health deterioration caused patient dependency on caregivers, along with feelings of burden, frustration, and distress. Good information provision and education improve caregiver involvement and patients’ self-management. Participants without informed caregiver support struggled with anxiety and disease management. Caregiver–patient relationship quality impacted the caregiver's involvement. In conclusion, patient dependency in advanced COPD leads to frustration and distress, highlighting the need for caregiver education and support. Effective information provision and early involvement of caregivers is essential to improving care quality, reducing distress, and supporting holistic palliative care.